Limitations of methods for measuring the concentration of human genomic DNA and oligonucleotide samples - Hua-Jun He; Erica V. Stein; Paul DeRose; Kenneth D. Cole (BioTechniques)
We compared different methods (absorbance, fluorescent dye-binding, and digital PCR) for measuring the concentrations of human genomic DNA from cultured cells and absorbance measurements of a synthetic DNA oligonucleotide. NIST Standard Reference Material (SRM) 2082, a pathlength absorbance standard, was used to benchmark the absorbance measurements done with microvolume spectrophotometers and a microvolume plate reader. Control absorbance values were measured on a high accuracy spectrophotometer and a NIST calibrated pathlength cuvette. Measurements of the human genomic DNA sample were done with several types of fluorescent dye binding assays using different DNA calibrators. The fluorescent dye binding methods gave different results for genomic DNA depending upon the type of DNA calibrator and the fluorescent dye that was used. The human genomic DNA sample was also characterized by using six different droplet digital PCR assays (amplicons located on different chromosomes) to measure the average copy number. Conversion of the digital PCR data to copy numbers was sensitive to the droplet size used for calculations and conversion to mass concentration was dependent upon the molecular weight of the human genome used for the calculations. The results from the different methods were compared and the caveats for each measurement method were discussed.